2020
DOI: 10.1007/s00264-020-04833-1
|View full text |Cite
|
Sign up to set email alerts
|

High platelet-to-lymphocyte ratio predicts poor survival of elderly patients with hip fracture

Abstract: Purpose The platelet-to-lymphocyte ratio (PLR) has been extensively studied in various diseases. However, the relationship between PLR and hip fracture remains unknown. The aim of this study was to evaluate whether PLR would be an independent prognostic factor in elderly hip fracture patients. Methods Between January 2014 and December 2018, a retrospective cohort study was conducted in a orthopaedic centre, China. A total of 460 hip fracture patients were included. PLR was calculated as the ratio of platelet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 43 publications
2
33
3
Order By: Relevance
“…The PLR is an effective predictor of cardiovascular and rheumatic diseases as has been demonstrated in many studies [13,15]. In addition, PLR has been reported to be associated with the prognosis of many severe injuries, dementia, and malignancies in recent years [10,16,26 [27,28].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The PLR is an effective predictor of cardiovascular and rheumatic diseases as has been demonstrated in many studies [13,15]. In addition, PLR has been reported to be associated with the prognosis of many severe injuries, dementia, and malignancies in recent years [10,16,26 [27,28].…”
Section: Discussionmentioning
confidence: 97%
“…The PLR and SII indicators have been widely studied in recent years as immunoin ammatory indicators as they are easy to obtain and cost-effective in clinical application. The PLR has great value in predicting the severity and mortality in many diseases such as hip fracture, in ammatory diseases, malignancy, systemic lupus erythematosus, and cardiovascular disease [10][11][12]15]. Moreover, the SII has been associated with the prognosis of malignancies, post-traumatic thrombosis, and fractures following osteoporosis [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent data showed that both NLR and PLR are reliable preoperative predictive markers of the postoperative overall survival and recurrence-free survival in patients with hepatocellular carcinoma [26]. Previously, few studies have tested the usefulness of PLR and NLR for predicting the outcomes in trauma patients [27][28][29][30][31][32]. However, the use of these ratios has not yet been evaluated in patients with abdominal trauma.…”
Section: Introductionmentioning
confidence: 99%